Minat Berwirausaha Sosial Dikalangan Mahasiswa - Purbo Jadmiko (Universitas Pendidikan Nasional, 2020)
ABSTRACTThis study aims to determine the direct effect of empathy and social support on the social entrepreneurship intention at Bung Hatta University students. A total of 208 samples were used in this study. The results of research testing show that empathy has no effect on interest in social entrepreneurship. While social support shows a positive and significant effect on social entrepreneurial interest. Discussions on the model of forming social interest in entrepreneurship among students were discussed in this study.